2021
DOI: 10.3390/electronics10202481
|View full text |Cite
|
Sign up to set email alerts
|

Applying Sentiment Product Reviews and Visualization for BI Systems in Vietnamese E-Commerce Website: Focusing on Vietnamese Context

Abstract: Product reviews become more important in the buying decision-making process of customers. Exploiting and analyzing customer product reviews in sentiments also become an advantage for businesses and researchers in e-commerce platforms. This study proposes a sentiment evaluation model of customer reviews by extracting objects, emotional words for emotional level analysis, using machine learning algorithms. The research object is the Vietnamese language, which has special semantic structures and characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Wang, Pan, Dahlmeier, and Xiao (2016) 2018) used a sequencelabeling approach in conjunction with Bidirectional Recurrent Neural Networks (BRNN) and Conditional Random Fields (CRF) to extract opinion targets and assess their sentiment simultaneously so as to analyze smartphone reviews on YouTube and e-commerce. Le and Huh (2021) utilized customer reviews on Tiki with various products and services to solve the emotional analysis issue through a deep learning method with long short-term memory neural network LSTM (belong to RNN), combined with CBOW, and TF-IDF techniques.…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang, Pan, Dahlmeier, and Xiao (2016) 2018) used a sequencelabeling approach in conjunction with Bidirectional Recurrent Neural Networks (BRNN) and Conditional Random Fields (CRF) to extract opinion targets and assess their sentiment simultaneously so as to analyze smartphone reviews on YouTube and e-commerce. Le and Huh (2021) utilized customer reviews on Tiki with various products and services to solve the emotional analysis issue through a deep learning method with long short-term memory neural network LSTM (belong to RNN), combined with CBOW, and TF-IDF techniques.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Furthermore, Kotler's model contains five stages of the buying decision process which also showed some essential factors like appearance, price, brand, quality, and social media review (Kotler, 2000). In addition, the previous studies involving e-commerce field extracted aspects such as price (cost), quality, satisfy, shipment, design, package, fragrance, and so on (Clara, Adiwijaya, & Purbolaksono, 2020;Le & Huh, 2021;Nandal et al, 2020). Based-on the previous studies, this study continued surveying vagan food and identified food's features as well as customers' behavior relevant to the dataset to propose the five aspects for the model.…”
Section: Phase 3: Analyzing Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Korean lacks language resources such as machine-readable dictionaries and sense-tagged corpora, compared with English. Therefore, in order to overcome the limitations of these linguistic resources in minority languages such as Korean and Vietnamese, it is urgent to study a method for clarification of vocabulary [5].…”
Section: Introductionmentioning
confidence: 99%